Angiogenesis in patients with psoriasis and psoriatic arthritis: cell-mediated and humoral mechanisms, its role in pathogenesis, and searching for promising therapeutic targets - T.V. Korotaeva (Современная ревматология)
Modern concepts of the role of angiogenesis in pathogenesis of psoriasis and psoriatic arthritis (PsA) are analyzed. The features of cell-mediated and humoral immune responses resulting in proliferation of synovial membrane and vessel overgrowth in patients with this pathology are discussed. A number of angiogenesis mediators, pro-angiogenic cytokines, growth factors, matrix metalloproteinases, etc. are shown to be involved in progression of neovascularization. The role of tumor necrosis factor α as a key therapeutic target for treatment of psoriasis and PsA is emphasized. Drugs inhibiting some stages of angiogenesis, which are either used in clinical practice or are being developed, are discussed.